RHEUMAORTOPEDICAL AID TO THE POPULATION OF RUSSIAN FEDERATION - L L Zhadenov; V A Mitrofanov; N V Artemova (Научно-практическая ревматология)
Analysis of the work of the Republican arthrologic center of Saratov Research Institute of Traumatology and Orthopedics was done. The reasons of the absence of timely and adequate rheumoorthopaedic care were assessed. The objectives for further improvement of rheumoorlhopedic service were presented.